Aesthetic Normativity and the Acquisition of Empirical Concepts - Geiger, Ido (Con-Textos Kantianos. International Journal of Philosophy, 2020)
In the Introduction to the Critique of the Power of Judgment, Kant claims that the Critique of Pure Reason accounted for the necessary conditions of experience and knowledge in general, but that it was not a complete transcendental account of the possibility of a particular empirical experience of objects and knowledge of empirical laws of nature. To fill this gap the third Critique puts forward, as an additional transcendental condition, the regulative principle of the purposiveness of nature. In this paper, I will attempt to show how Kant’s account of pure aesthetic judgment can be read as articulating an aesthetic non-conceptual condition of the search for the conceptual order of nature and so as constituting an essential part of the account of the transcendental conditions of empirical experience and knowledge.